AN INVESTIGATION FOR ECONOMICAL WAY OF RECYCLE OF SOLID WASTES FROM A DORMITORY - Kocer, Nilufer (Nacar); Isik, Hilal (Arslanoglu) (Pamukkale Univ, 2005)
Collection, transportion, reuse, recycle and proper disposal solid wastes is major environmental problems for local administrations. At present, the most appropriate disposal method of solid waste from the point of view of economy and environment is recycle at the source. In this study the applicability of solid wastes recovery system which is one of the waste disposal methods for student dormitory wastes having economical values has been evaluated in Elazig. The results of this study were evaluated and benefits of 'seperation of wastes at the source' system for student dormitory in Elazig were discussed and cost analysis of recovered materials was realized.
Keywords: Solid waste; Recyle; Seperation at source point; Cost analysis; Dormitory; Elazig